Peran Sistem Penjaminan Mutu Dinas Pendidikan Kabupaten Gresik Dalam Meningkatkan Mutu Pendidikan Di Pendidikan Sekolah Dasar Di Gresik - Ach. Khusnan; Muslimatul Alfiyah (Jurnal Pendidikan Agama Islam Miazhar, 2025)
This study aims to analyze the implementation of the quality assurance system carried out by the Gresik Regency Education Office in improving the quality of education in Elementary school education (SD). Through a collaborative and strategic approach, the Education Office provides support in the form of training, mentoring, and evaluation to improve the quality of human resources and educational facilities. The obstacles faced include less than optimal coordination between institutions, limited human resources, and lack of valid quality data. The solutions sought include strengthening cross-agency cooperation, using information technology, and increasing the internal capacity of madrasahs. This study is expected to provide recommendations for policies to improve the quality of education at the elementary level, especially in SD. The results of the study indicate that sustainable and integrated efforts will accelerate the improvement of the quality of education that is equitable and sustainable.